Cerebrospinal fluid oligoclonal IgM test in routine practice: Comparison with quantitative assessment of intrathecal IgM synthesis - Zeman, David; Kušnierová, Pavlína; Všianský, František; Reguliová, Katarína; Škutová, Monika; Woznicová, Ivana; Zapletalová, Olga; Hradílek, Pavel (Clinica chimica acta; international journal of clinical chemistry, 2020)
BACKGROUND: Intrathecal IgM synthesis demonstrated either as cerebrospinal fluid (CSF)-restricted oligoclonal (o-) IgM bands or calculated using various formulas has been linked to more aggressive multiple sclerosis (MS) course. However, the proportion of MS patients showing intrathecal IgM synthesis varies largely between studies. We aimed to explore the relation between different formulas and results of o-IgM, and to assess the frequency of o-IgM bands in an unselected series of samples. METHODS: 432 samples were analyzed for o-IgM, o-IgG and quantitative measures of IgM and IgG synthesis. IgM index and formulas of Reiber, Auer and Öhman were compared to the result of the o-IgM test. RESULTS: At the cut-off commonly used, the non-linear formulas for intrathecal synthesis were specific (>94%) but rather insensitive (<40% even at a cut-off of 4 CSF-restricted bands) compared to o-IgM. No significant difference was noted in the performance of different formulas. At a cut-off of 4 bands, 61% of MS patients, but none of the controls were positive for o-IgM. CONCLUSIONS: Formulas for intrathecal IgM synthesis are insensitive compared to o-IgM. We propose to evaluate samples with 2 or 3 extra-CSF IgM bands as borderline and only samples with 4 or more as definitely positive.
Keywords: Multiple Sclerosis; imunoglobulin M; Immunoglobulin M; Humans; oligoklonální proužky; Oligoclonal Bands; Intrathecal synthesis; Oligoclonal IgM; roztroušená skleróza; Cerebrospinal fluid; lidé; Multiple sclerosis